2020
DOI: 10.1001/jamanetworkopen.2020.31756
|View full text |Cite
|
Sign up to set email alerts
|

Household Transmission of SARS-CoV-2

Abstract: Key Points Question What is the household secondary attack rate for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)? Findings In this meta-analysis of 54 studies with 77 758 participants, the estimated overall household secondary attack rate was 16.6%, higher than observed secondary attack rates for SARS-CoV and Middle East respiratory syndrome coronavirus. Controlling for differences across studies, secondary attack rates were higher in househ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

46
261
6
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 618 publications
(356 citation statements)
references
References 116 publications
46
261
6
6
Order By: Relevance
“…In the present study, the absence of identified child-to-staff member transmission during the 13-week study period suggests in-school spread was uncommon. This apparent lack of transmission is consistent with recent research ( 5 ), which found an asymptomatic attack rate of only 0.7% within households and a lower rate of transmission from children than from adults. However, this study was unable to rule out asymptomatic transmission within the school setting because surveillance testing was not conducted.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the absence of identified child-to-staff member transmission during the 13-week study period suggests in-school spread was uncommon. This apparent lack of transmission is consistent with recent research ( 5 ), which found an asymptomatic attack rate of only 0.7% within households and a lower rate of transmission from children than from adults. However, this study was unable to rule out asymptomatic transmission within the school setting because surveillance testing was not conducted.…”
Section: Discussionsupporting
confidence: 92%
“…Age-dependent infectivity might be associated with household lifestyles, family structure, and clinical conditions ( 9 ). Meta-analysis showed that the sex of the primary case-patient was not associated with transmission ( 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…The primary cases of infectiousness defined by age, sex, and symptoms were less studied in the different settings. Furthermore, there were few reports of SAR among asymptomatic primary cases ( 3 , 5 , 6 ). Therefore, we estimated the SAR of COVID-19 and assessed the effects of age and sex of primary cases, symptoms of primary cases, and the time between diagnosis and symptom onset for primary cases on infectiousness in familial clusters.…”
mentioning
confidence: 99%
“…Lewis et al find a rate of 28% in Wisconsin and Utah [ 41 ], while Grijalva et al found 53% in Wisconsin and Tennessee [ 42 ]. A recent review by Madewell et al [ 43 ] reports values between 4–44%. Curmei et al’s review [ 44 ] attempts to collect all these estimates and correct them upwards by accounting for false negative rates of diagnostic tests and for asymptomatic infections, resulting in estimates between ~10–55%.…”
Section: Discussionmentioning
confidence: 99%